Tissue sealants for the prevention of lymphoceles after radical inguinal lymph node dissection in patients with melanoma: A systematic review and individual patient data meta‐analysis. Issue 6 (23rd January 2019) - Gerken, Andreas L. H.; Dobroschke, Jakob; Reißfelder, Christoph; Hetjens, Svetlana; Braun, Volker; Di Monta, Gianlica; Jakob, Jens; Hohenberger, Peter; Nowak, Kai; Herrle, Florian
Abstract : Background and Objectives: Postoperative lymphoceles and further wound complications occur frequently after radical inguinal lymph node dissection (ILND). In various studies, tissue sealants have shown to reduce the incidence of postoperative morbidity. Methods: A systematic review and meta‐analysis of randomized controlled trials (RCTs) investigating the effectiveness of tissue sealants in reducing the incidence of postoperative lymphoceles following ILND in patients with melanoma was conducted. Individual patient data was requested to pool the data for meta‐analysis appropriately. Results: Thousand seven hundred twenty‐nine manuscripts were screened for eligibility. Six RCTs published between 1986 and 2012 were identified including 194 patients for ILND. Only four RCTs were included in the meta‐analysis. No study properly defined the term "lymphocele." Tissue sealants failed to influence the duration of drain placement (mean difference [MD] = −3.05 days; z = 1.18; P = 0.24), total drainage volume (MD = 598.39 mL; z = 1.49; P = 0.14), the incidence of postoperative seroma, wound infection and skin necrosis. Conclusions: No improvement was identified with the use of tissue sealants, however, a valid comparison of the results of included trials was difficult owing to the lack of a definition of the term "lymphocele." Other surgical techniques and trials using validated endpoint definitions are required to reevaluate these findings.